2012
DOI: 10.1371/journal.pone.0048071
|View full text |Cite
|
Sign up to set email alerts
|

Knockout of Insulin-Like Growth Factor-1 Receptor Impairs Distal Lung Morphogenesis

Abstract: BackgroundInsulin-like growth factors (IGF-I and -II) are pleiotropic regulators of somatic growth and development in vertebrate species. Endocrine and paracrine effects of both hormones are mediated by a common IGF type 1 receptor (IGF-1R). Lethal respiratory failure in neonatal IGF-1R knockout mice suggested a particular role for this receptor in pulmonary development, and we therefore investigated the consequences of IGF-1R inactivation in lung tissue.Methods and FindingsWe first generated compound heterozy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 30 publications
3
57
1
Order By: Relevance
“…IGF-1/IGF-1R has been shown to be required for normal lung development, pulmonary vascularization, and proper alveolarization (8,15,16). In our study, we observed that lung IGF-1 levels in mice increased significantly after birth before returning to baseline at around 2 weeks of age, coinciding with the period of postnatal alveolarization in mice and consistent with an important function of IGF-1 in lung development after birth ( Figure 1A).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…IGF-1/IGF-1R has been shown to be required for normal lung development, pulmonary vascularization, and proper alveolarization (8,15,16). In our study, we observed that lung IGF-1 levels in mice increased significantly after birth before returning to baseline at around 2 weeks of age, coinciding with the period of postnatal alveolarization in mice and consistent with an important function of IGF-1 in lung development after birth ( Figure 1A).…”
Section: Discussionsupporting
confidence: 85%
“…Reverse transcription was performed using Superscript III (Invitrogen) and oligo (dT) [12][13][14][15][16][17][18] primers, and real-time quantitative PCR was set up containing Power SYBR Green Master Mix (Applied Biosystems, Foster City, CA). The sequences for IGF-1 exon 4-specific primers used are shown in Table 1, and b-actin was used as an endogenous control.…”
Section: Osi-906 Administration To Neonatal Micementioning
confidence: 99%
“…Classical Igf1r-deficient (IGF1R knockout) mice die at birth presumably due to respiratory failure and exhibit a 55 % decrease in body weight compared to wild type controls. Prenatal IGF1R knockout embryos exhibit growth retardation and generalized developmental abnormalities, comprising hypoplasia, altered central nervous system, abnormal skin formation, delayed bone development, reduced pancreatic beta-cells, failure of testicular determination, lung immaturity and cochlear defects (Bonnette and Hadsell 2001;Epaud et al 2012;Liu et al 1993;Nef et al 2003;Okano et al 2011;Scolnick et al 2008;Withers et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The lung tissue sections were selected for quantitating airspace in lung. The airspace enragement of the lung was measured using a digitized image tool [17]. The pulmonary inflammation index was graded as previously described [18].…”
Section: Uplc-esi-ms Analysismentioning
confidence: 99%